Intoxicación en bovinos por nitratos y nitritos acumulados en pasto pará (Brachiaria mutica (Forsk) Stapf) (1981)
Bovine intoxication by nitrate and nitrites accumulated in Para grass (Brachiaria mutica) is described in The Dorada area being the results confirmed by toxicological methods. Grass accumulation of nitrates are related with soil fertility and climatic conditions.